2022
DOI: 10.1128/jmbe.00328-21
|View full text |Cite
|
Sign up to set email alerts
|

An Upper-Division, Remote Microbiology Laboratory That Blends Virtual and Hands-on Components to Promote Student Success during the COVID-19 Pandemic

Abstract: The COVID-19 shutdown forced many institutions of higher education to shift in-person teaching to emergency remote teaching. This was particularly challenging for laboratory courses, where students are expected to learn hands-on skills needed for their career goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A virtual microbiology laboratory developed for pharmacy students was found to be as effective as the wet laboratory 47 . Students who used the virtual microbiology laboratory had a greater understanding of microbiology concepts, demonstrated proficiency and better performance 2 . Virtual simulation operation was a teaching tool found effective in teaching clinical skills as well and garnered positive response from the students 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A virtual microbiology laboratory developed for pharmacy students was found to be as effective as the wet laboratory 47 . Students who used the virtual microbiology laboratory had a greater understanding of microbiology concepts, demonstrated proficiency and better performance 2 . Virtual simulation operation was a teaching tool found effective in teaching clinical skills as well and garnered positive response from the students 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Through this research, the retention, revision, and new implementation of digital tools to enhance in-person or digital learning environments has transformed biology laboratory education (Bontanelli et al, 2020;Sousa et al, 2022). While many positive advancements in biology education and digital tool use were revealed during the pandemic transition to online instruction (Guzman-Cole et al, 2022;Sweeney et al, 2022), barriers and "deficiencies in the use of technology in education" were also exposed (Bawa, 2020;Chidzonga et al, 2022, p 2;Sarvary et al, 2022;Wilkerson et al, 2022).…”
Section: Digital Tool Retention: Post Pandemicmentioning
confidence: 92%
“…The identification of digital tools, such as immersive virtual reality (VR) (Wilkerson et al, 2022), virtual simulations (Guzman-Cole et al, 2022Tripepi, 2021), videos of laboratory activities and dissections (Burnham et al, 2023;Jayanth et al, 2022), Researcher Avatar (RA) activity (Galvadon et al, 2022), Storyline 360 interactive lab activities (Sweeney et al, 2022), and at-home microscopes or lab kits (Lionetti et al, 2022;Guzman-Cole et al, 2022), used during the pandemic has been shown to provide adequate and valuable alternatives to in-person lab instruction. Additionally, online labs allow students to work at their own pace in distractionfree learning environments while preserving the educational goals of biology lab courses (Sweeney et al, 2022).…”
Section: Digital Tool Retention: Post Pandemicmentioning
confidence: 99%
See 2 more Smart Citations